2016
DOI: 10.1002/adfm.201505019
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Flexible Multilayer MoS2 Transistors on Solution‐Based Polyimide Substrates

Abstract: Transition metal dichalcogenides (TMDs) layers of molecular thickness, in particular molybdenum disulfide (MoS2), become increasingly important as active elements for mechanically flexible/stretchable electronics owing to their relatively high carrier mobility, wide bandgap, and mechanical flexibility. Although the superior electronic properties of TMD transistors are usually integrated into rigid silicon wafers or glass substrates, the achievement of similar device performance on flexible substrates remains q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 70 publications
0
72
0
Order By: Relevance
“…Compared to zero‐band‐gap graphene, MoS 2 is recently considered as one of the most promising 2D materials for replacing the widely explored 2D graphene, because it is a semiconducting, 2D layered transition‐metal dichalcogenide, with a band gap changing from 1.2 eV in the bulk to 1.8 eV in monolayers . With these intriguing electronic and optical properties, and special atomically scalable structure advantages, the 2D MoS 2 ‐based devices exhibit high promise for many state‐of‐the‐art electronic applications, such as photovoltaic solar cells, flexible electronics, advanced ultrasmall transistors, integrated circuits, etc. Recently, we note that Arnold et al have reported an interesting work to mimic neurotransmitter release by using interface trapping/detrapping in MoS 2 transistors .…”
mentioning
confidence: 99%
“…Compared to zero‐band‐gap graphene, MoS 2 is recently considered as one of the most promising 2D materials for replacing the widely explored 2D graphene, because it is a semiconducting, 2D layered transition‐metal dichalcogenide, with a band gap changing from 1.2 eV in the bulk to 1.8 eV in monolayers . With these intriguing electronic and optical properties, and special atomically scalable structure advantages, the 2D MoS 2 ‐based devices exhibit high promise for many state‐of‐the‐art electronic applications, such as photovoltaic solar cells, flexible electronics, advanced ultrasmall transistors, integrated circuits, etc. Recently, we note that Arnold et al have reported an interesting work to mimic neurotransmitter release by using interface trapping/detrapping in MoS 2 transistors .…”
mentioning
confidence: 99%
“…By using conventional solid‐state high‐k dielectrics such as HfO 2 on flexible substrates, MoS 2 transistors achieved high ON/OFF ratios, more than 10 7 , and low field mobilities of 30 cm 2 V −1 s −1 , with bending radii down to 1 mm . Recent work successfully used a solution‐based polyimide (PI) flexible substrate in which laser‐welded silver nanowires are embedded, together with a hybrid organic/inorganic gate insulator and multilayers of MoS 2 , resulting in transistors that have field‐effect‐mobilities as high as 141 cm 2 V −1 s −1 and stable performance after 1000 bending cycles, as shown in Figure d,e …”
Section: Flexible Device Applicationsmentioning
confidence: 99%
“…j) Analysis of mechanical robustness of flexible BP transistor with normalized extrinsic f T measured under uniaxial tensile strain up to 1.5%. a), d), e) Reproduced with permission . Copyright 2016, Wiley.…”
Section: Flexible Device Applicationsmentioning
confidence: 99%
“…The 2D MoS 2 is one of the most promising semiconductors for next generation electronics due to its tunable bandgap, favorable electronic mobility, excellent optoelectronic properties, and good thermal and chemical and mechanical stabilities . Scalable fabrication of 2D films is the precondition for manufacturing of post‐ Moore's law large‐scale integrated devices.…”
Section: Introductionmentioning
confidence: 99%